2011
DOI: 10.1308/147870811x13137608455253
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after treatment of laryngeal carcinoma: a single centre cross-sectional study

Abstract: The mainstays of treatment for head and neck cancers include surgery, chemotherapy and radiotherapy given alone or in combination. However, the side effects of these treatments are multifactorial in nature, causing substantial physical as well as psychosocial morbidity.1,2 Their location inherently affects life's basic and vital functions including breathing, feeding and oral communication. Furthermore, altered appearance, difficulty in swallowing and pain as a result of treatment can cause problems with socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Sex was not a significant factor in a study by de Graeff et al (2000), but age had an influence on fatigue, physical functioning, social eating, and speech; as older patients had worse scores. Williamson et al (2011) found no evidence of an age effect when they evaluated HRQOL of patients with head and neck cancer, but they did not include sex analyses in their study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sex was not a significant factor in a study by de Graeff et al (2000), but age had an influence on fatigue, physical functioning, social eating, and speech; as older patients had worse scores. Williamson et al (2011) found no evidence of an age effect when they evaluated HRQOL of patients with head and neck cancer, but they did not include sex analyses in their study.…”
Section: Discussionmentioning
confidence: 95%
“…Sex was not a significant factor in a study by de Graeff et al (2000), but age had an influence on fatigue, physical functioning, social eating, and speech; as older patients had worse scores. Williamson et al (2011) found no evidence of an age effect when they evaluated HRQOL of patients with head and neck cancer, but they did not include sex analyses in their study.HRQOL was associated with patients' age in LĂČpez-Jornets et al study (2012), who evaluated 94 patients undergoing treatment for head and neck cancer in Spain. In their study females had a slight tendency to score worse than males for some functioning scales with symptoms, financial difficulty and sexuality.…”
mentioning
confidence: 95%
“…Mitra et al divided QOL into special branches that need to be taken care of in order to achieve as good results as possible [16]. Swallowing, voice, airway control, nutrition, pain, mucositis control, xerostomia, taste and auditory function, wound care (fistula and carotid rupture), osteoradionecrosis, dermatitis and soft tissue damage, and psychological support seems to be the most important factors in proper life relief therapy [17].…”
Section: Quality Of Lifementioning
confidence: 99%
“…The objective of another study [4] was to identify the aspects of quality of life of patients with cancer of the larynx after the different forms of treatment. Quality of life was assessed by applying the "University of Washington Quality of Life" -(UW-QOL), questionnaire to 41 individuals treated with combined modalities (surgery and chemotherapy/radiotherapy in 11 patients), primary radiotherapy ( n = 26), and chemoradiotherapy ( n = 4).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%